Hubungan Tingkat Kecemasan dan Dukungan Sosial dengan Maternal Self Efficacy Pada Ibu Primigravida dalam Persiapan Persalinan Masa Covid-19 di Klinik Bidan Syifa Bekasi - Mutiara Tobing (2021)
The anxiety felt by primigravida mothers will be different from the anxiety felt by multigravida mothers. During pregnancy support is very important from the husband's support. Especially in primigravida pregnant women. Maternal self-efficacy is part of the concept of self-efficacy, namely the mother's perspective on her confidence to carry out her duties and role as parents in caring for and caring for babies in all situations. The purpose of this study was to determine the relationship between anxiety and social support with maternal self-efficacy in primigravida mothers in preparation for childbirth during the COVID-19 pandemic at the Syifa Midwife Clinic, Bekasi City. The research design used was cross sectional with 108 samples and the sampling technique used was concecutive sampling. Collecting data through a questionnaire consisting of four parts, namely MSE, MSPSS, HARS. The results of the bivariate test of anxiety levels with Maternal self-efficacy (p value = 0.001), while social support with Maternal self-efficacy (p value = 0.018). It is expected that pregnant women, especially primigravida, will be able to control their emotions to reduce stress and be supported also by their partners, family, and environment to provide support in any form so that mothers feel more confident in preparing to become a mother.